2000
DOI: 10.1046/j.1464-410x.2000.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing urodynamic pattern from infancy to adolescence in boys with posterior urethral valves

Abstract: Objective To determine whether bladder dysfunction in boys with posterior urethral valves (PUV) changes from a uniform pattern of hypercontractility during infancy to the hypocontractility found in adolescence, by reviewing serial urodynamic studies. Patients and methods Thirty boys with PUV and no voiding symptoms underwent a total of 86 urodynamic tests (mean 2.8 each). The first urodynamic study was undertaken at 1–4 years of age in 15 boys and at 5–13 years in 15. They were re‐evaluated at least 3 years la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 13 publications
1
46
0
1
Order By: Relevance
“…A variety of UDS diagnoses before and after treatment were reported. 23,24 The ICI-CDT recommends to consider UDS on an individual basis and recommends further investigation to standardize UDS in boys with (suspected) posterior urethral valves and to determine the (clinical) value of UDS in these cases.…”
Section: Urodynamic Testing In Children (Neurologically Affected or Nmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of UDS diagnoses before and after treatment were reported. 23,24 The ICI-CDT recommends to consider UDS on an individual basis and recommends further investigation to standardize UDS in boys with (suspected) posterior urethral valves and to determine the (clinical) value of UDS in these cases.…”
Section: Urodynamic Testing In Children (Neurologically Affected or Nmentioning
confidence: 99%
“…A variety of UDS diagnoses before and after treatment were reported. 23,24 The ICI-CDT recommends to consider UDS on an individual basis and recommends further investigation to standardize UDS in boys with (suspected) posterior urethral valves and to determine the (clinical) value of UDS in these cases.The ICI-CDT has found only a few studies that characterize the change in LUT function following bladder neck reconstruction in patients with persistent UI after reconstruction for bladder extrophy and no studies have correlated UI with bladder capacity, compliance, DO, and/or LPP, after treatment. 25,26 The ICI-CDT recommends to consider the relevance of UDS after or before (secondary) reconstruction for bladder extrophy on an individualized basis and recommends further investigation to standardize UDS and to determine the (clinical) value of UDS in these cases.…”
mentioning
confidence: 99%
“…Thirty-eight to 70% of neonatally diagnosed and treated PUV patients develop the "valve bladder syndrome," which represents the spectrum of bladder dysfunction that manifests many years after definitive treatment of valves. 12 Gennaro and colleagues studied the natural history of voiding patterns using urodynamic studies in 30 boys treated for PUV. Bladder dysfunction was present in 70%, and changed from unstable/hypercontractile in infancy, to hypocontractile in childhood, to a true myogenic failure in adolescence, 12 despite early valve ablation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Gennaro and colleagues studied the natural history of voiding patterns using urodynamic studies in 30 boys treated for PUV. Bladder dysfunction was present in 70%, and changed from unstable/hypercontractile in infancy, to hypocontractile in childhood, to a true myogenic failure in adolescence, 12 despite early valve ablation. Holmdahl suggested that these 3 urodynamic findings are variations of the same basic pattern evolving with time toward decompensation in early presenters, despite early correction of obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Close and colleagues [11], [12] reviewed the outcome in 31 boys, of whom 23 underwent valve ablation in the first year of life and compared them with eight boys who had MacKinnon AE: High diversion in PUV a high diversion but without giving clear indications for the choice of procedure. Progressive renal failure was not prevented in either group, which implies that this is determined by pre-existing damage.…”
Section: Bladder Dysfunctionmentioning
confidence: 99%